Impact of rising greenhouse gas concentrations on future tropical ozone and UV exposure. Issue 6 (21st March 2016) - Meul, Stefanie; Dameris, Martin; Langematz, Ulrike; Abalichin, Janna; Kerschbaumer, Andreas; Kubin, Anne; Oberländer‐Hayn, Sophie
Abstract: Future projections of tropical total column ozone (TCO) are challenging, as its evolution is affected not only by the expected decline of ozone depleting substances but also by the uncertain increase of greenhouse gas (GHG) emissions. To assess the range of tropical TCO projections, we analyze simulations with a chemistry‐climate model forced by three different GHG scenarios (Representative Concentration Pathway (RCP) 4.5, RCP6.0, and RCP8.5). We find that tropical TCO will be lower by the end of the 21st century compared to the 1960s in all scenarios with the largest decrease in the medium RCP6.0 scenario. Uncertainties of the projected TCO changes arise from the magnitude of stratospheric column decrease and tropospheric ozone increase which both strongly vary between the scenarios. In the three scenario simulations the stratospheric column decrease is not compensated by the increase in tropospheric ozone. The concomitant increase in harmful ultraviolet irradiance reaches up to 15% in specific regions in the RCP6.0 scenario. Key Points: Tropical total column ozone is projected to decrease due to rising greenhouse gas concentrations Consequently, a significant increase of harmful UV radiation is predicted for parts of the tropics Largest uncertainties exist about the future amount of tropical tropospheric ozone